Extrapancreatic effects of incretin hormones: evidence for weight‐independent changes in morphological aspects and oxidative status in insulin‐sensitive organs of the obese nondiabetic Zucker rat (ZFR). Issue 15 (10th August 2016) - Colin, Ides M.; Colin, Henri; Dufour, Ines; Gielen, Charles‐Edouard; Many, Marie‐Christine; Saey, Jean; Knoops, Bernard; Gérard, Anne‐Catherine
Abstract: Incretin‐based therapies are widely used to treat type 2 diabetes. Although hypoglycemic actions of incretins are mostly due to their insulinotropic/glucagonostatic effects, they may also influence extrapancreatic metabolism. We administered exendin‐4 (Ex‐4), a long‐acting glucagon‐like peptide receptor agonist, at low dose (0.1 nmol/kg/day) for a short period (10 days), in obese nondiabetic fa/fa Zucker rats (ZFRs). Ex‐4‐treated ZFRs were compared to vehicle (saline)‐treated ZFRs and vehicle‐ and Ex‐4‐treated lean rats (LRs). Blood glucose levels were measured at days 0, 9, and 10. Ingested food and animal weight were recorded daily. On the day of sacrifice (d10), blood was sampled along with liver, epididymal, subcutaneous, brown adipose, and skeletal muscle tissues from animals fasted for 24 h. Plasma insulin and blood glucose levels, food intake, and body and epididymal fat weight were unchanged, but gross morphological changes were observed in insulin‐sensitive tissues. The average size of hepatocytes was significantly lower in Ex‐4‐treated ZFRs, associated with decreased number and size of lipid droplets and 4‐hydroxy‐2‐nonenal (HNE) staining, a marker of oxidative stress (OS). Myocytes, which were smaller in ZFRs than in LRs, were significantly enlarged and depleted of lipid droplets in Ex‐4‐treated ZFRs. Weak HNE staining was increased by Ex‐4. A similar observation was made in brown adipose tissue, whereas the elevated HNE staining observed in epididymal adipocytes of ZFRs, suggestive of strong OS, was decreased by Ex‐4. These results suggest that incretins by acting on OS in insulin‐sensitive tissues may contribute to weight‐independent improvement in insulin sensitivity. Abstract : Beyond the well‐known insulinotropic actions of incretins, the results presented in this article suggest that incretins may also favorably influence glucose metabolism by improving insulin sensitivity in insulin‐sensitive organs (liver, adipocytes, and myocytes).